2018
DOI: 10.15405/epsbs.2018.02.107
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Implementing Practice-Oriented Higher Education Programs Based On Stakeholders Feedback

Abstract: The article covers the issues of higher education development in the framework of innovative economy and the role of practice-oriented education technologies in this process. It presents substantial characteristics of successful international practice-oriented models, which potential can be used to solve problems that occur in the national system of education. It is shown that the successful implementation of practice-oriented programs involves the development of various forms of interaction between business a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…On the one hand, it is the preservation of the fundamental nature of education, and on the other hand, the constant updating of its content by strengthening practical focus. In such conditions, the team of authors considers the most effective strengthening of the role of practice-oriented [1,2,3,[4][5][6][7][8][9][10][11][12][13][14] technologies in the educational process, that is, a harmonious combination of theoretical knowledge in solving practical issues. Without completely reducing the importance of the theoretical block, the practice-oriented approach aims educational organizations [18,[19][20][21][22][23][24] to develop such forms of educational process that allow the effective use of case study [4,[6][7][8], master classes, trainings, business games [5], design and problematic techniques, independent research (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, it is the preservation of the fundamental nature of education, and on the other hand, the constant updating of its content by strengthening practical focus. In such conditions, the team of authors considers the most effective strengthening of the role of practice-oriented [1,2,3,[4][5][6][7][8][9][10][11][12][13][14] technologies in the educational process, that is, a harmonious combination of theoretical knowledge in solving practical issues. Without completely reducing the importance of the theoretical block, the practice-oriented approach aims educational organizations [18,[19][20][21][22][23][24] to develop such forms of educational process that allow the effective use of case study [4,[6][7][8], master classes, trainings, business games [5], design and problematic techniques, independent research (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The empirical basis of the study was the study and analysis of Russian and international experience of using practiceoriented [1,2,3,[4][5][6][7][8][9][10][11][12][13][14] technologies in the educational process of leading universities. The methodological basis of the study was the scientific and educational literature, which was recited in the list of sources.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the analysis, it was found that all bad habits that undermine health (alcohol, smoking and others) are determined not only by DNA, but primarily by lifestyle, which in turn depends on the level of education. Higher education helps people eat better and not depend on bad habits (Margarov, Mitrofanova, Konovalova, Mitrofanova, & Trubitsyn, 2018).…”
Section: General Patterns At All Stages Of Life Forcementioning
confidence: 99%